Spectrophotometric Kinetic Studies of the Reaction between Triphenylphosphine, Dialkyl Acetylenedicarboxylates and NH-Acids - MOSTAFA HABIBI KHORASSANI, S.; T. MAGHSOODLOU, MALEK; EBRAHIMI, ALI; MORADIAN, MAJID; ZAKARIANEZHAD, MOHAMMAD (Asian Journal of Chemistry, 2010)
The major objective of the work undertaken were to carry out kinetic studies of the reaction between triphenylphosphine and dialkyl acetylenedicarboxylates in the presence of indole derivatives (as a NH-acid). To determine the kinetic parameters of the reaction, it was monitored by UV spectrophotometer. The second order fits were automatically drawn by the software associated with a Cary UV spectrophotometer model Bio-300 at appropriate wavelength. The values of the second order rate constant (k2) were automatically calculated using standard equations within the program. At the temperature range studied the dependence of the second order rate constant (Ln k) on reciprocal temperature was in agreement with Arrhenius equation. This provide the relevant plots to calculate the activation energy of all reactions. Furthermore useful information was obtained from studies of the effect of solvent and different alkyl groups within the dialkyl acetylenedicarboxylates on the rate of reactions.